PRODUCTION IMPROVEMENT OF NATURALLY FRACTURE RESERVOIR THE X FIELD USING MULTILATERAL WELL - Feni Maulindani (NIM 22205006), Sri
ABSTRACT: Naturally fractured reservoir give the most important part of oil and gas reserves and production in the world. Where more than 40percent oil and gas reserve exist in naturally fracture reservoir and have a large productivity. Characteristic of this kind reservoir is unique, because there are two mechanism production in this reservoir, that is reservoir fluid flow to the matrix than flow to the fracture and then flow to well. Modeling of naturally fracture reservoir in this study is using Warren and Root model with dual porosity model. In this study reservoir have two porosity and two permeability that is matrix and fracture. According to the study such as core lab and well test analysis indicated that the X field is a naturally fracture reservoir. Characterization of naturally fracture reservoir at X field from well test yield omega and lambda, which is the most important parameter to characterize the naturally fracture reservoir. There are two well in the X field there are X 1 and X 2.